2016
DOI: 10.1088/1361-6528/28/5/055205
|View full text |Cite
|
Sign up to set email alerts
|

Steep switching characteristics of single-gated feedback field-effect transistors

Abstract: In this study, we propose newly designed feedback field-effect transistors that utilize the positive feedback of charge carriers in single-gated silicon channels to achieve steep switching behaviors. The band diagram, I-V characteristics, subthreshold swing, and on/off current ratio are analyzed using a commercial device simulator. Our proposed feedback field-effect transistors exhibit subthreshold swings of less than 0.1 mV dec, an on/off current ratio of approximately 10, and an on-current of approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…2 a). Second, as the gate voltage increases from 0.00 to 1.00 V in the gated p-n-p-n diode structure, the conduction band (the valence band) edge in the gated channel region is lowered from 1.03 to 0.37 eV (from − 0.02 to − 0.69 eV), allowing the injection of electrons into the potential well in the conduction band of the non-gated channel region 26 . The potential barrier modulation by the input voltage stimulates the electron injection from the source to the channel region; the injected electrons accumulate in the potential well in the non-gated channel region.…”
Section: Resultsmentioning
confidence: 99%
“…2 a). Second, as the gate voltage increases from 0.00 to 1.00 V in the gated p-n-p-n diode structure, the conduction band (the valence band) edge in the gated channel region is lowered from 1.03 to 0.37 eV (from − 0.02 to − 0.69 eV), allowing the injection of electrons into the potential well in the conduction band of the non-gated channel region 26 . The potential barrier modulation by the input voltage stimulates the electron injection from the source to the channel region; the injected electrons accumulate in the potential well in the non-gated channel region.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the potential barrier heights are varied by the ITCs when the same voltages are applied. A higher potential barrier height implies that the positive feedback loop is eliminated by the gate voltage with a lower absolute value 3 , 4 , 6 . The differences in the potential barrier height based on the ITCs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most FBFET designs have complex fabrication procedures 1 , 2 , or additional gate electrodes 3 , 5 , 6 . Recently, single gate-all-around (GAA) FBFETs with p + - n + - i - n + Si nanowire (SiNW) channels have been proposed to reduce complex device structures and additional gate electrodes 4 . These FBFETs demonstrate high performance because the GAA SiNW structure improves the gate controllability of the potential barrier height in the channel region.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, simulation studies have demonstrated that the low standby power consumption and reliability of one-transistor SRAM (1T-SRAM) cells, each of which consists of a single-gated feedback field-effect transistor (FBFET), provide a promising possibility for the future of memory devices 17 . Compared with metal–oxide–semiconductor field-effect transistors (MOSFETs) conventionally used in SRAM cells, FBFETs, operating with a positive feedback loop mechanism, exhibit an extremely low subthreshold swing (~ 0 mV/dec), high on/off current ratios, and bi-stable states 18 – 22 . Moreover, the use of 1T-SRAM cells reduces usage area on chips when compared with conventional 6T-SRAM cells constructed with MOSFETs.…”
Section: Introductionmentioning
confidence: 99%